Tobacco smoking and mortality among Aboriginal and Torres Strait Islander adults in Australia. (25th January 2021) - Thurber, Katherine A; Banks, Emily; Joshy, Grace; Soga, Kay; Marmor, Alexandra; Benton, Glen; White, Sarah L; Eades, Sandra; Maddox, Raglan; Calma, Tom; Lovett, Raymond
Abstract: Background: Despite generally high smoking prevalences, stemming from colonization, the relationship of smoking to mortality has not been quantified reliably in an Indigenous population. We investigate smoking and mortality among Aboriginal and Torres Strait Islander adults in Australia, where current adult daily smoking prevalence is 40.2%. Methods: A prospective study of 1388 cardiovascular disease- and cancer-free Aboriginal adults aged ≥45 years, of the 267 153 45 and Up Study participants randomly sampled from the New South Wales general population over 2006–09. Questionnaire and mortality data were linked (through the Centre for Health Record Linkage) to mid-2019. Adjusted hazard ratios (called relative risks, RRs) for all-cause mortality—among current- and past- versus never-smokers—were estimated overall, by smoking intensity and by age at cessation. Smoking-attributable fractions and associated deaths were estimated. Results: Over 14 586 person-years' follow-up (median 10.6 years), 162 deaths accrued. Mortality RRs [95% confidence interval (CI)] were 3.90 (2.52–6.04) for current- and 1.95 (1.32–2.90) for past- versus never-smokers, with age heterogeneity. RRs increased with smoking intensity, to 4.29 (2.15–8.57) in current-smokers of ≥25 cigarettes/day. Compared with never-smokers, RRs were 1.48 (0.85–2.57) for those quitting at <45 years of age and 2.21 (1.29–3.80) at 45–54 years. Never-smokers lived an average >10 years longer than current-smokers. Around half of deaths among adults aged ≥45 years were attributable to smoking, exceeding 10 000 deaths in the past decade. Conclusions: In this population, >80% of never-smokers would survive to 75 years, versus ∼40% of current-smokers. Quitting at all ages examined had substantial benefits versus continuing smoking; those quitting before age 45 years had mortality risks similar to never-smokers. Smoking causes half of deaths in older Aboriginal and Torres Strait Islander adults; Indigenous tobacco control must receive increased priority.